Type I Chiari malformation presenting orthostatic syncope who treated with decompressive surgery - Hyun-Seung Shin; Jeong A Kim; Dong-Seok Kim; Joon Soo Lee (Korean Pediatric Society, 2016)
Chiari malformations are a congenital anomaly of the hindbrain. The most common, Chiari malformation type I (CM-I), is characterized by herniation of the cerebellar tonsils extending at least 3 mm below the plane of the foramen magnum. Consequently, CM-I is associated with hydrocephalus and symptoms involving compression of the cervicomedullary junction by ectopic tonsils. Several studies have reported the clinical symptoms associated with CM-I, including suboccipital headache, weakness in the upper extremities, facial numbness, loss of temperature sensation, ataxia, diplopia, dysarthria, dysphagia, vomiting, vertigo, nystagmus, and tinnitus. Syncope is one of the rarest presentations in patients with CM-I. There are many hypotheses regarding the causes of syncope in patients with CM-I; however, the mechanisms are not clearly understood. Although surgical decompression for CM-I in patients with syncope has yielded good clinical results in some studies, such cases are rarely reported. We report a case of orthostatic syncope in a patient with CM-I who was treated with surgical intervention.